Prevalance of psychiatric and physical morbidity in elderly sentenced prisoners in England and Wales - Fazel, Seena B. (University of Edinburgh, 2002)
BACKGROUND: The number of elderly prisoners has been increasing in Western countries over the past decade. In England and Wales, the population of those aged 60 and over in prison has more than trebled in the last decade, and there are over 1000 elderly men in prison. There are no published studies of psychiatric morbidity in this population. METHOD: A stratified sample of 203 male sentenced prisoners aged over 59, from 15 prisons in England and Wales, representing one in five men in this age group, was interviewed using semistructured standardised instruments for psychiatric illness, personality disorder, and acute and chronic physical ill health. In addition, major illnesses and types of medication were recorded from their prison medical notes and prison reception health screen. The psychiatric characteristics of the sex offenders interviewed were compared with the non-sex offenders. RESULTS: 53% (95% Cl, 46-60%) of the elderly prisoners had a psychiatric diagnosis. The most common diagnoses were personality disorder (30% [24-36%]) and depressive illness (30% [23-36%]). No differences were found between the sex offenders (n=101) and the nonsex offenders (n=102) in the rates of psychiatric illness or personality disorder. Significant differences emerged at the level of personality traits with sex offenders having more schizoid and obsessive-compulsive traits compared with non-sex offenders. 85% of the elderly prisoners had one or more major illnesses reported in their medical records, and 83% reported at least one chronic illness on interview. The most common physical illnesses were cardiovascular, musculoskeletal and respiratory. CONCLUSIONS: The prevalence of depressive illness in this sample of elderly male prisoners was five times greater than found in other studies of younger adult male prisoners and community elderly men. The rate of physical illness in elderly prisoners was also higher than in other studies of younger prisoners and in surveys of the general population of a similar age. The growing numbers of elderly in prison pose specific challenges for prison health care services. In particular, underdetected, undertreated depressive illness in elderly prisoners is an increasing public health problem.
The prevalance of psychiatric and physical morbidity in elderly sentenced prisoners in England and Wales
Keywords: Psychiatry